Biomechanical Behavior Evaluation of a Novel Hybrid Occlusal Splint-Mouthguard for Contact Sports: 3D-FEA - Kalman, Les; Dal Piva, Amanda Maria de Oliveira; de Queiroz, Talita Suelen [UNESP]; Tribst, João Paulo Mendes (MDPI, 2022)
Background: Orofacial injuries are common occurrences during contact sports activities. However, there is an absence of data regarding the performance of hybrid occlusal splint mouthguards (HMG), especially during compressive loading. This study amid to evaluate the biomechanical effects of wearing a conventional custom mouthguard (MG) or the HMG on the teeth, bone, and the device itself. Methods: To evaluate the total deformation and stress concentration, a skull model was selected and duplicated to receive two different designs of mouthguard device: one model received a MG with 4-mm thickness and the other received a novel HMG with the same thickness. Both models were subdivided into finite elements. The frictionless contacts were used, and a nonlinear analysis was performed simulating the compressive loading in occlusion. Results: The results were presented in von-Mises stress maps (MPa) and total deformation (mm). A higher stress concentration in teeth was observed for the model with the conventional MG, while the HMG design displayed a promising mechanical response with lower stress magnitude. The HMG design displayed a higher magnitude of stress on its occlusal portion (7.05 MPa) than the MG design (6.19 MPa). Conclusion: The hybrid mouthguard (HMG) reduced (1) jaw displacement during chewing and (2) the generated stresses in maxillary and mandibular teeth.
Keywords: Athletic injuries; Finite element analysis; Mouthguard; Occlusal splint; Trauma